Stereoselective allylation of isatinimines with γ-substituted allylboronic acids. (27th April 2021) - Tan, Qiuyuan; Wang, Xinqiao; Fu, Lin; He, Ling; Zhang, Min
Graphical abstract: Highlights: Asymmetric allylation of ketimines with achiral γ -substituted allylboron reagents. Access to chiral homoallylamine bearing adjacent quaternary–tertiary stereocenters. Chiral amino alcohol was used as imine precursor and chirality source. Abstract: A highly efficient asymmetric allylboration of isatinimines with γ -substituted allylboronic acids under metal-free conditions was disclosed. Employing chiral amino alcohol as the chirality controller, the reaction proceeded with high efficiency and excellent stereoselectivity, providing a broad range of chiral 3-allyl-3-hydroxyethylamino oxindoles containing adjacent quaternary–tertiary stereocenters in high yields with excellent diastereoselectivities (up to 92% yield, >20:1 d.r.)